Quality Assurance in West African TVET Institutions: A Brief Literature Review - Odjo, Cosme Zinsou; Kaoti, Cordula; Oyewusi, Alaba Oluwatoyin (Journal of Technical and Vocational Education and Training, 2024)
The study reviews the role of quality assurance in Technical and Vocational Education and Training (TVET) systems in supporting economic development, enhancing labor market competitiveness, and meeting industry expectations. The authors use a desk research strategy, focusing on document review and qualitative content analysis to analyze credible reports on the role of quality assurance in TVET to promote competent workforce. As per findings, quality assurance in TVET institutions is crucial to ensuring that graduates possess the necessary skills and competencies for the workforce, reducing skills gaps and enhancing employability. It aligns TVET programs with industry standards, enabling graduates to contribute effectively to the workforce. Quality assurance mechanisms also enhance the credibility and reputation of TVET institutions, increasing their attractiveness to students and employers. It helps produce highly skilled individuals, contributing to the country’s economic development and global competitiveness. However, the TVET sector in West Africa faces several challenges, including inadequate infrastructures, curriculum relevance, teaching and learning quality, limited industry collaboration, and lack of quality assurance mechanisms. To address these issues, the authors suggest some innovative dimensions of quality standards to strengthen and improve quality assurance in TVET institutions. These quality standards include leadership, governance, management, physical environment, human resources, curriculum, student participation, access, equity, career guidance, financial management, program evaluation, research, innovation and development. All of these are interrelated, thereby spurring the overall quality and effectiveness of TVET programs and institutions.